SPACES AND “NOT-SPACES” IN THE ZHADAN’S PROSE - Vypasniak, Halyna (Літературний процес: методологія, імена, тенденції, 2019)
The paper analyses the symbolic features of spaces of Serhiy Zhadan’s prose. The main attention is paid to the novel “Voroshylovhrad” and the name of the city that doesn’t exist on the geographic maps anymore. Most spaces, such as a petrol station or abandoned airfield, could be defined as non-places (the term of M. Auge). For M. Auge it’s a type of space that shows the hybridity of our life. It’s basically the transit places. That is why there are no emotions connected with those non-places: no special stories, no narrative, that could create the place itself. The analysed novel by Serhiy Zhadan assures that even those places that weren’t noticed by most people and were treated by them as non-places, were really precious for others because of their personal memories and their past time, spent there. The paper also analyses the special features of the novel according M. Auge’s term the “anthropologic place”. It’s a place that represents an identity of native group that used to live there and shows the power of a connection between the place and its inhabitants. It’s also a place, where they can feel themselves and make their own rules. Those things make places like the petrol station, worth to be defended from intrusions. DOI: https://doi.org/10.28925/2412-2475.2019.1315